Pengaruh Akupresur Titik PC6 Terhadap Penurunan Emesis Ibu Hamil - -, Huzaima; Heroyanto; Sri Dewi Haryati; Rofiqo Larasati Philip (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2023)
Emesis gravidarum is one of the discomforts that mothers often feel in early pregnancy, characterized by symptoms of nausea and vomiting. These symptoms usually occur 6 weeks after the first day of the last menstruation and last for approximately 10 weeks, but in some cases they can continue into the second and third trimesters of pregnancy. The incidence of nausea and vomiting in the world is 70% -80% of the number of pregnant women. Acupressure is known as a traditional Chinese therapy method for healing Emesis by using massage techniques on the meridian points of certain body parts. The purpose of this study was to determine the effect of pressing the PC6 point on reducing emesis in pregnant women. The design of this study was one group pretest post test design used for 20 pregnant women with emetic complaints, then analyzed using a paired sample t-test. The results obtained were a p-value of 0.003, which means that there is an effect of acupressure by emphasizing the pericardium meridian (PC) 6 on reducing emesis in pregnant women. Keywords: Acupressure, Emesis, Pregnancy.